Sistem Penunjang Keputusan Penerimaan Bantuan RASKIN dengan Metode SAW (Simple Addictive Weighting) - Sari Geovani; Nanda Pratama2 (Ikatan Ahli Informatika Indonesia, 2020)
Poverty is a social problem that is inevitable in various parts of the world, both in developed and developing countries. In overcoming the problem of poverty, many programs have been carried out by the government especially in Indonesia to minimize poverty, both in the form of material and non-material assistance. One of the government assistance programs that is still running today is the assistance of Poor Rice (RASKIN). Rice is the staple food of the Indonesian population and therefore in 2002 the Indonesian government launched the Poor Rice Program (RASKIN). The Poor Rice Program is also carried out in Jorong Sawah, the Corner of Selayo, in the process of selecting and determining the families of RASKIN beneficiaries, the Jorong apparatus is still implementing a manual system. Due to the large number of people entitled to receive assistance, while the amount of aid distributed is limited, the Head of Jorong Sawah Corner of Selayo has difficulty in determining which families are most entitled to receive RASKIN assistance. Computers are one alternative to advanced technology that can help deal with problems that exist in various fields. Therefore to solve the above problem, a decision support system for Raskin Assistance Acceptance was built using the SAW (Simple Adictive Weigting) method. With the development of this decision support system can help and facilitate the Selective Head of Jorong Sawah Corner in order to produce the right decision.